Montgomery : D-Day commander - Hamilton, Nigel (Military profiles., 2007)
"This study of military leadership follows British field marshal Bernard Law Montgomery's military career from his cadet days and service in World War I to his great victories of World War II - including his defeat of the great German panzer commander, Erwin Rommel, at Alamein - to his time as chief of the Imperial General Staff and his outspoken and controversial views in life on apartheid and communism." "Nigel Hamilton presents a brilliant, arrogant Montgomery, who refused to bow to authority and skated on the edge of dismissal. Despite this, Montgomery became one of the two most successful Allied field generals in World War II. From North Africa through the invasion of Sicily, he and Gen. George S. Patton routed the Germans in battle, with the rival Patton as a thrusting cavalryman and Montgomery as an infantry commander devoted to applying massive force at the vital point. Hamilton contends that Montgomery's planning and leadership transformed Operation Overlord from a second front project doomed to fail, into a successful Allied invasion plan." "The war ended for Monty on May 4, 1945, when he accepted the surrender of all German forces in the north, and, Hamilton contends, it was Montgomery's arrogance that "made D-Day the most decisive and triumphant battle of the democracies in the twentieth century.""--Jacket